Comparative analysis of outer membrane vesicles from uropathogenic Escherichia coli reveal the role of aromatic amino acids synthesis proteins in motility - LiangZhe Liu; Carmen Oi Kwan Law; Qichang Nie; Hoa Quynh Pham; Haiying Ma; Liang Zhang; Pak Leung Ho; Terrence Chi-Kong Lau (Elsevier, 2023)
Uropathogenic Escherichia coli (UPEC) are causative agent that causes urinary tract infections (UTIs) and the recent emergence of multidrug resistance (MDR) of UPEC increases the burden on the community. Recent studies of bacterial outer membrane vesicles (OMV) identified various factors including proteins, nucleic acids, and small molecules which provided inter-cellular communication within the bacterial population. However, the components of UPEC-specific OMVs and their functional role remain unclear. Here, we systematically determined the proteomes of UPEC-OMVs and identified the specific components that provide functions to the recipient bacteria. Based on the functional network of OMVs' proteomes, a group of signaling peptides was found in all OMVs which provide communication among bacteria. Moreover, we demonstrated that treatment with UPEC-OMVs affected the motility and biofilm formation of the recipient bacteria, and further identified aromatic amino acid (AAA) biosynthesis proteins as the key factors to provide their movement.